Y chromosomes: born to be destroyed. - Steinemann, S.; Steinemann, M. (BioEssays, 2005)
Suppression of recombination is the prerequisite for stable genetically determined sex systems. A consequence of suppression of recombination is the strong bias in the distribution of transposable elements (TEs), mostly retrotransposons. Our results and those from others indicate that the major force driving the degeneration of Y chromosomes are retrotransposons in remodelling former euchromatic chromosome structures into heterochromatic ones. We put forward the following hypotheses. (1) A massive accumulation of retrotransposons occurs early in non-recombining regions. (2) Heterochromatic nucleation centres are formed as a genomic defence mechanism against invasive parasitic elements. The newly established nucleation centres become epigenetically inherited. (3) Spreading of heterochromatin from the nucleation centres into flanking regions induces, in an adaptive process, transcriptional gene silencing of neighbourhood genes that could either be still intact or in an already eroded condition. (4) Constitutive silenced genes are not under the same genetic selection pressure as active genes. They are more exposed to the decay process. (5) Gene dosage balance is re-established by the parallel evolution of dosage compensation mechanisms.